Implementasi Nilai-nilai al-Qur’an dalam Mencegah Penyebaran Berita Bohong di Era Digital - Marsila; Islamiyah (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2025)
The phenomenon of fake news or hoaxes has become a serious challenge in the digital era, drastically changing the order of social communication. This article analyzes the implementation of the values ??of the Qur'an to prevent the spread of hoaxes, highlighting the current digital ethics crisis. Many internet users spread information without verification, even though the Qur'an through Q.S. An-Nur: 19 provides a strong warning against the spread of vile deeds. An examination of the meaning of the word ifk in Islamic terminology shows that hoaxes are not just ordinary lies, but major slander that damages honor and social order. Islam teaches the importance of tabayyun (clarification of information) according to Q.S. Al-Hujurat: 6, husnuzhon (having good intentions) in Q.S. Al-Hujurat: 12, as well as the principles of honesty, responsibility, and trustworthiness in social media. These principles are the foundation of responsible social media ethics. The application of Qur'anic values ??in dealing with hoaxes requires the active role of all parties: the government with strict regulations, educational institutions with digital literacy integration, and the general public with the culture of "filtering before sharing." Technology-based solutions such as fact-checking applications and positive campaigns on social media also need to be encouraged. By bringing the values ??of the Qur'an to life, Muslims can build a healthy, dignified, and faith-based digital community, making social media a field for preaching and goodness, not a means of sin.